Identification of selection signatures involved in performance traits in a paternal broiler line - Almeida, Octávio Augusto Costa (2019)
Natural and artificial selection cause changes in certain regions of the genome resulting in selection signatures. Thus, is expected to identify genes associated with the traits under selection in such regions. Selection signatures may be identified using different methodologies, and some are based on detecting of contiguous sequences of homozygous identical-by-descent haplotypes, called runs of homozygosity (ROH), or estimating fixation index (FST) of genomic windows that indicates genetic differentiation. In our study, we aimed to identify selection signatures in a paternal broiler line and to investigate the genes annotated in these regions as well as the biological phenomena involved. For such purpose, ROH and FST-based analysis were performed using whole genome sequence of twenty eight chickens from two different generations. ROH analysis identified homozygous regions of short and moderate length. Analyzing ROH patterns it was observed regions commonly shared among some animals and changes in ROH abundance and length between the two generations. The results also suggests that WGS outperforms SNPchip data, however the number of individuals analyzed must be properly chosen. FST-based analysis revealed genetic differentiation in some genomic windows. Annotation of the consensus regions of ROH and FST windows counted for many genes of which some were previously associated with traits of economic interest, such as APOB, IGF1, IGFBP2, POMC, PPARG, and ZNF423. Overrepresentation analysis of the genes resulted in biological terms of skeletal muscle, matrilin proteins, adipose tissue, hyperglycemia and diabetes, Salmonella infections and tyrosine. Therefore, suggested that ancient and recent selection in TT line acted over regions affecting performance traits.